Konvergenz der Verteilungen von Produkte unabhängiger zufälliger Veränderlicher - Bakštys, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бакштис. Сходимость законов распределения произведений независимых случайных величин A. Bakštys. Nepriklausomų atsitiktinių dydžių sandaugų pasiskirstymo dėsnių konvergavimas